Influence of training and selection on postural stability and its relationship with sport level in judo practitioners aged 11-14 years - Jaworski, J.; Lech, G.; Witkowski, K.; Bujas, P.; Szczepanik, K.; Piepiora, P. (Frontiers in Psychology, 2023)
The aim of this study is to determine the influence of training and selection on postural stability and its relationship with the sports level of judo practitioners aged 11-14 years. The study group consisted of 21 children judokas, aged 11-12, and 80 of their non-training peers, as well as 19 adolescent judokas, aged 13-14, and 76 of their non-training peers. The judokas were surveyed during regional championships. The level of achievement was determined by the place taken in the tournament. The balance was assessed with the use of a CQ Stab 2P stabilographic platform (CQ Elektronik System, Poland). The device recorded the position of the foot center of pressure (COP) from 6 sensors; 3 of them being located in each platform plate. The following parameters describing the movement of the foot COP were analyzed: total path length calculated in both axes (SP); mean COP inclination (MA), size of the surface area delineated by COP (SA); mean COP frequency (MF). Significantly higher values of SP, MA, and SA were noted in non-training children (aged 11-12), while MF values were significantly higher in young judokas. The same regularity was found in the older age group. Upon comparing the means between children judokas and adolescent judokas, significant differences were noted in the case of SP and MF. In both cases, higher mean values were found in the younger judoka group. A similar comparison in the non-training group indicates statistically significant better values of all analyzed indicators in the 13-14 year-old group, except for MF. Upon examining the relationship between the values of the parameters characterizing the balance level and the sports level, both in the group of training children and adolescents, insignificant values of correlation coefficients were obtained.